USM ARCHAEOLOGY TEAM CONFIRMS PREHISTORIC PRESENCE ON LOCAL SHORES - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
SEBERANG PERAI UTARA, 25 April 2017 The archaeology team from Universiti Sains Malaysia (USM) has unearthed skeletal remains estimated to be at least 5,000 years old at a construction site here. The team from the USM Centre for Global Archaeological Research (CGAR) led by its Director, Professor Dato’ Dr. Mohd Mokhtar Saidin, has provided their expertise in uncovering and assessing the prehistoric remains.